Backwashing-induced nitrous oxide emissions in denitrifying biofilters: Dissolved N2O accumulation, physical stripping, and enzymatic imbalance - Jiabo Chen; Huiling Chen; Dingyu Hu; Ziding Ao; Ruobing Li; Baohua Tang; Hongchen Wang; Lu Qi; Guohua Liu (Bioresource Technology, 2026)

Water environmental carrying capacity and driving factors in Yangtze estuary: PCA-copula and Shapley value with salinity zoning - Haibiao Zhu; Jinjie Li; Xu Zhao; Qi Wu; Yuan Fang; Ruobing Han; Yonglu Feng; Ying Tang; Hong Huang (Estuarine, Coastal and Shelf Science, 2026)

Superior removal of phthalate acid esters from water using a magnetic PIM-1 adsorbent - Ruobing Jia; Shunying Li; Keda Guo; Shiqi Yang; Yingying Zhang; Qiangqiang Xu; Hong Ye; Hehe Li; Shuangyang Li; Shengpeng Shi (Chemical Engineering Journal, 2026)

Amino acid functionalization-induced dipole regulation suppresses carrier decay in perylene diimide to enhance photocatalytic activity - Weili Yu; Ningjie Fang; Ruobing Wang; Zhaobing Liu; Jinhui Li; Jieyuan Li; Hongxiang Li; Heng Wang; Jie Xiong; Yinghao Chu (Journal of Hazardous Materials, 2026)

β-Eudesmol Alleviates Inflammatory Injury in Septic Cardiomyopathy Through Enhancing GSK3B Activity to Inhibiting IL-17-Mediated Chemokine Expression - Sihua Jiang; Zhuoqing Dai; Tingting Pang; Ruobing Li; Xiaosong Wang; Hangqi Zhu; Guolin Song (Biochemical Genetics, 2026)

A high-ion-conductivity hydrogel electrolyte based on sodium starch phosphate for dendrite-suppressed, long-cycling flexible zinc-air batteries - Zhihao Liu; Siyao Zhang; Yuanna Sun; Ruobing Tian; Peiguo Zha; Jiaqi Hu; Xinyue Wang; Jianlin Yuan; Yan Jiang; Qingshan Li (Chemical Engineering Journal, 2026)

Effect of Bangia fusco-purpurea polysaccharides fermented with Enterococcus faecium on enhancing intestinal barrier function - Wenqin Yang; Yuanfan Yang; Ruobing Dai; Yujia Ou; Tao Hong; Zhipeng Li; Yanbing Zhu; Hui Ni; Zedong Jiang; Mingjing Zheng (Food Bioscience, 2026)

Crafting cellulose hollow microspheres with cellulose nanosheets - Wenxuan Lei; Heng Huang; Ruobing Liang; Guoping Li; Pan Chen; Jiechun Xiang; Ang Lu (Carbohydrate Polymers, 2026)

The incorporation of methylated nucleotides can significantly improve the stability of dsRNA and efficiency of pests control - Xuezhi Zhang; Yinuo Wang; Xuexia Miao; Ruobing Guan; Haichao Li (Chemical Engineering Journal, 2026)

Research on HaNRX, a potential RNAi target gene in Helicoverpa armigera - Rui Han; Dongdong Chu; Zhibin Hao; Haichao Li; Xuexia Miao; Shiheng An; Ruobing Guan (Pesticide Biochemistry and Physiology, 2026)

Pollutant-specific reactive species fingerprints: elucidating differential photocatalytic antibiotic degradation mechanisms in ZnIn2S4-based systems - Ruobing Wang; Zhaobing Liu; Weili Yu; Ningjie Fang; Jinhui Li; Yinghao Chu (Journal of Environmental Management, 2026)

Microphase separation-induced conductivity enhancement in anti-swelling amphiphilic ionogels for multimodal sensing - Xueming Tang; Jiahao Liu; Ruobing Tian; Yu Zhang; Xinli Wang; Lei Zhang; Zhaoqing Li; Jianlin Yuan; Yan Jiang; Yuanna Sun (Chemical Engineering Journal, 2026)

Molecular characterization of the (+)ssRNA genome of an ourmia-like virus infecting the plant-pathogenic fungus Botryosphaeria dothidea - Shunpei Xie; Haiyan Wu; Fengyue Gong; Xiuyuan Sun; Ruobing Kong; Qinzhou Ma; Yashuang Guo; Haiqiang Li; Lirong Yang; Chao Xu; Meng Zhang (Archives of Virology, 2026)

In situ revealed photogenerated charge transfer in FeOOH-BiOI/KCN heterojunction photocatalysts for efficient photocatalysis-self-Fenton degradation of antibiotics - Tongtong Zhang; Zhiheng Xia; Ruobing Li; Hongchen Wang; Tao Zhang; Lu Qi; Yunfei Tan; Yingxu Liu; Aihua Gao; Baogui Wang; Xiangnan Li (Journal of Environmental Sciences, 2026)

CO2-responsive gels for enhanced oil recovery and carbon sequestration: A comprehensive review of design and applications - Jianing Yu; Xu Li; Ruobing Qiao; Liming Zheng; Nasir Khan; Haifeng He; Zhimin Peng; Yanhua Yu (Journal of Environmental Chemical Engineering, 2025)

Synergistic and continuous driving of Fe(III)/Fe(II) cycle by electron-rich organic contaminants and peroxymonosulfate: Homogeneous feasibility and heterogeneous application - Jin Chai; Yu Wei; Haoran Kong; Hui Liu; Zhuohan Li; Junshuo Huang; Ruobing Pi; Zhe Yang; Xuhui Sun (Chemical Engineering Journal, 2025)

A review of the extraction technologies, structural characterization, chemical modification, and pharmacological effects of Ganoderma lucidum polysaccharides - ChenXue Li; RuoBing Zhang; Bing Tian; Bing Liu; Yu Mei; WenLan Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Interactions of sesamol with starches of different amylose to amylopectin ratios during co-gelatinization condition - Xiaoqiang Li; Hongyue Zhao; Ruobing Jia; Jia Cao; Yaxing Xie; Zeyu Peng; Jianjun Cheng (Carbohydrate Polymers, 2025)

Organic carbon released from tire chips enhances pyrite particle-based autotrophic denitrification of water - Zhiheng Xia; Tongtong Zhang; Ruobing Li; Qinsheng Zhang; Ziding Ao; Guohua Liu; Lu Qi; Hongchen Wang (Journal of Environmental Management, 2025)

Multi-omics insights into 6PPD- and 6PPDQ-induced gut-liver axis disruption and non-alcoholic fatty liver disease progression in zebrafish (Danio rerio) - Yu Feng; Hongyi Xian; Ruobing Bai; Zhiming Li; Hao Li; Long Zhang; Xiyun Huang; Yuji Huang; Boxuan Liang; Yanhong Deng; Xiaohong Yang; Xiaoqing Chen; et al. (Journal of Hazardous Materials, 2025)

Lactic acid bacteria fermentation: A novel and promising pathway to lower the uric acid production of seaweed food (Porphyra haitanensis) - Yuting Dong; Xinyao Chao; Ruobing Li; Jinli Chen; Jinzhong Cai; Yang Yang; Yuanqing Lin (International Journal of Food Microbiology, 2025)

Sequential heterotrophy–dilution–photoinduction cultivation of Botryococcus sudeticus for enhanced squalene production - Ruobing Tan; Tao Yu; Lulu Yan; Weiliang Wang; Minxi Wan; Yuanguang Li (Algal Research, 2025)

Electroporation optimization for cell wall-deficient and cell-walled Chlamydomonas reinhardtii using response surface methodology - Minxi Wan; Ruobing Tan; Zining Wang; Weiliang Wang; Tao Yu; Yuanguang Li (Algal Research, 2025)

The role of developmental and climate factors in driving autumn phenology across the Northern Hemisphere - Shuping Ji; Shilong Ren; Xiaoyang Zhang; Ruobing Liu; Zhenyu Gao; Changchao Li; Lei Fang; Jinyue Chen; Xinfeng Wang; Guoqiang Wang; Qingzhu Zhang; Qiao Wang (Agricultural and Forest Meteorology, 2025)

The post-effects of landscape practices on spontaneous plants in urban parks - Chundi Chen; Ruobing Wang; Mingkun Chen; Juanjuan Zhao; He Li; Maria Ignatieva; Weiqi Zhou (Urban Forestry & Urban Greening, 2025)

Targets selection and field evaluation of an RNA biopesticide to control Phyllotreta striolata - Saibo Xu; Xuezhi Zhang; Yinuo Wang; Rui Han; Xuexia Miao; Haichao Li; Ruobing Guan (Pesticide Biochemistry and Physiology, 2025)

Experimental study on oil recovery characteristics of different CO2 flooding methods in sandstone reservoirs with NMR - Yonggang Ding; Lyu Qiao; Zhihong Li; Ruobing Luo; Guodong Han; Jingqiang Tan; Xin Liu (Fuel, 2025)

Effects of copper-based fungicides on the growth and tolerance of Helicoverpa armigera: implications for pest management - Wenhui Lu; Yuhao Liu; Ruobing Guan; Qing Zhai; Xiaoguang Liu; Wenli Zhao; Shiheng An; Xiang Li (Pesticide Biochemistry and Physiology, 2025)

Harnessing multi-target nanosweepers inhibiting β-amyloid aggregation, scavenging reactive oxygen species and overcoming the blood brain barrier for rescuing Alzheimer’s disease - Yixuan Wang; Chaoren Yan; Yuming Qi; Ruobing Zhao; Yan Wan; Zhaoyuan Lyu; Yansong Li; Zhijuan Wang; Changqing Li; Yuehe Lin; Qian Chen; Shichao Ding; et al. (Chemical Engineering Journal, 2025)

Investigation on the influence mechanism of N element doping on the photocatalytic properties of the g-C3N4@ZnCdS composite photocatalyst - Fucheng Yu; Ruobing Jiang; Xuying Duan; Jielin Zhang; Jinlong Ren; Chenchen Feng; Cuixia Li; Kechao Hu; Xiaogang Hou (Journal of Water Process Engineering, 2025)

Improving paste stabilities of cassava starch through molecular density after maltogenic amylase and transglucosidase - Shuo Sun; Ruobing Li; Dengyue Sun; Li Guo; Bo Cui; Feixue Zou (Food Chemistry, 2025)

Significant spatiotemporal changes in atmospheric particulate mercury pollution in China: Insights from meta-analysis and machine-learning - Haolin Wang; Tianshuai Li; Guoqiang Wang; Yanbo Peng; Qingzhu Zhang; Xinfeng Wang; Yuchao Ren; Ruobing Liu; Shuwan Yan; Qingpeng Meng; Yujia Wang; Qiao Wang (Science of The Total Environment, 2024)

Privacy-preserving multi-source semi-supervised domain adaptation for seizure prediction - Deng Liang; Aiping Liu; Le Wu; Chang Li; Ruobing Qian; Xun Chen (Cognitive Neurodynamics, 2024)

Magnetic adsorbents for removal of bisphenol A: Design strategies of materials and adsorption mechanisms - Ruobing Jia; Yingying Zhang; Shunying Li; Jun Wang; Jun Kang; Qiangqiang Xu; Hong Ye (Chemosphere, 2024)

Surface morphologic changes and mineral transformation mechanisms after CO2-brine-rock reaction in organic matter-rich ferroan shale - Xin Liu; Jingqiang Tan; Qixiang Wang; Hui Li; Guodong Han; Yonggang Ding; Xueqi Song; Ruobing Luo; Shihao Hua (Chemical Engineering Journal, 2024)

Gender-specific effects of polystyrene nanoplastic exposure on triclosan-induced reproductive toxicity in zebrafish (Danio rerio) - Zhiming Li; Hongyi Xian; Rongyi Ye; Yizhou Zhong; Boxuan Liang; Yuji Huang; Mingzhu Dai; Jie Guo; Shuqin Tang; Xiaohu Ren; Ruobing Bai; Yu Feng; et al. (Science of The Total Environment, 2024)

Water distribution in pore systems and its influences on gas-bearing property of deep shale: A case study of the Longmaxi Formation in the Luzhou area, southern Sichuan Basin - Yue Feng; Xianming Xiao; Ping Gao; Dongfeng Hu; Ruobing Liu; Gang Li; Chengang Lu; Qin Zhou (Marine and Petroleum Geology, 2024)

From cradle to grave: Deciphering sex-specific disruptions of the nervous and reproductive systems through interactions of 4-methylbenzylidene camphor and nanoplastics in adult zebrafish - Hongyi Xian; Zhiming Li; Ruobing Bai; Rongyi Ye; Yu Feng; Yizhou Zhong; Boxuan Liang; Yuji Huang; Jie Guo; Binjie Wang; Mingzhu Dai; Shuqin Tang; et al. (Journal of Hazardous Materials, 2024)

Preparation of novel gallic acid-based dummy-template molecularly imprinted polymer adsorbents for rapid adsorption of dibutyl phthalate from water - Shunying Li; Yuanhao Zhou; Qiangqiang Xu; Haoxiang Chen; Shengpeng Shi; Ruobing Jia; Yingying Zhang; Hong Ye (Environmental Pollution, 2024)

Expression profiles and characterization of microRNAs responding to chitin in Arthrobotrys oligospora - Ningxing Li; Yansen Sun; Yucheng Liu; Lixiang Wei; Jiahua Zhang; Nengxiu Li; Dianming Sun; Jian Jiao; Yufei Zuo; Ruobing Li; Xuepeng Cai; Jun Qiao; et al. (Archives of Microbiology, 2024)

The structural and functional properties of a novel enzyme-modified starch as an alternative to hydroxypropyl starch ether - Ruobing Li; Haiteng Tao; Congping Tan; Fang Yuan; Li Guo; Bo Cui; Yu Zhu; Feixue Zou; Pengfei Liu; Lu Lu (Food Hydrocolloids, 2024)

Effect of sheeting stress and heating on the molecular chain structure, size, and conformation of gluten proteins during noodle processing - Mengli Zhang; Ruobing Jia; Meng Ma; Qingjie Sun; Man Li; Fengwei Xie (Food Hydrocolloids, 2024)

Versatile wheat gluten: functional properties and application in the food-related industry - Mengli Zhang; Ruobing Jia; Meng Ma; Tianbao Yang; Qingjie Sun; Man Li (Critical Reviews in Food Science and Nutrition, 2023)

4-Methylbenzylidene camphor triggers estrogenic effects via the brain-liver-gonad axis in zebrafish larvae - Hongyi Xian; Zhiming Li; Rongyi Ye; Mingzhu Dai; Yu Feng; Ruobing Bai; Jie Guo; Xiliang Yan; Xingfen Yang; Da Chen; Zhenlie Huang (Environmental Pollution, 2023)

Fault detection and calibration for building energy system using Bayesian inference and sparse autoencoder: A case study in photovoltaic thermal heat pump system - Peng Wang; Congwei Li; Ruobing Liang; Sungmin Yoon; Song Mu; Yuchuan Liu (Energy and Buildings, 2023)

Restoration of sedimentary environment and geochemical features of deep marine Longmaxi shale and its significance for shale gas: A case study of the Dingshan area in the Sichuan Basin, South China - Yue Feng; Xianming Xiao; Ping Gao; Enze Wang; Dongfeng Hu; Ruobing Liu; Gang Li; Chengang Lu (Marine and Petroleum Geology, 2023)

Effect of riboflavin and carbon black co-modified fillers coupled with alkaline pretreatment on anaerobic digestion of waste activated sludge - Ruobing Li; Hong Lu; Ze Fu; Xiaolei Wang; Qiansheng Li; Jiti Zhou (Environmental Research, 2023)

Gas in place and its controlling factors of deep shale of the Wufeng-Longmaxi Formations in the Dingshan area, Sichuan Basin - Ping Gao; Xianming Xiao; Dongfeng Hu; Ruobing Liu; Fei Li; Qin Zhou; Yidong Cai; Tao Yuan; Guangming Meng (Frontiers of Earth Science, 2023)

Archean–Paleoproterozoic magmatism in the Xishui Complex, South China: Implications for crustal evolution and amalgamation of the Yangtze Block - Tian Zhao; Guang Zhu; Ruobing Luo; Chenglong Xie; Shuai Zhang; Huifeng Hu; Jiayi Gu; Feiyang Tian; Chengchuan Gu; Yunjian Li (Journal of Asian Earth Sciences, 2023)

Interactions between large-scale strike-slip intersecting faults: Implication from the Tan–Lu and Xiangfan–Guangji fault zones in eastern China - Tian Zhao; Guang Zhu; Jin Ye; Zhengyan Xu; Biwei Xiang; Chengchuan Gu; Yunjian Li; Ruobing Luo; Chengran Dai; Huifeng Hu (International Geology Review, 2022)

Insight into maize gene expression profiles responses to symbiotic bacteria derived from Helicoverpa armigera and Ostrinia furnacalis - Haichao Li; Yongjun Wei; Guohui Yuan; Ruobing Guan (Archives of Microbiology, 2022)

Humoral immune durability of IgG for anti-SARS-CoV-2 in the normal pregnant women in Wuhan, China - Hongwen Ma; Jing Peng; Ruobing Li; Xuan Zheng; Shiyao Wu; Heng Yin; Min Li; Liu Qin; Fei Tang; Yun Zhao (Immunologic Research, 2021)

Clinical and microbiological characteristics of adults with hospital-acquired pneumonia: a 10-year prospective observational study in China - Yuyao Yin; Chunjiang Zhao; Henan Li; Longyang Jin; Qi Wang; Ruobing Wang; Yawei Zhang; Jiangang Zhang; Hui Wang; Chunxia Yang; Bin Cao; Yingmei Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Complete genome sequence of a novel rhabdo-like virus from the Chinese black cutworm Agrotis ipsilon (Lepidoptera: Noctuidae) - Su Chen; Haichao Li; Guohui Yuan; Ruobing Guan; Tong Li (Archives of Virology, 2020)

Development of Timolol-Loaded Galactosylated Chitosan Nanoparticles and Evaluation of Their Potential for Ocular Drug Delivery - Ruobing Zhao; Jing Li; Jingyi Wang; Zhenya Yin; Yongtao Zhu; Wei Liu (AAPS PharmSciTech, 2017)

RNAi pest control and enhanced BT insecticidal efficiency achieved by dsRNA of chymotrypsin-like genes in Ostrinia furnacalis - Ruobing Guan; Haichao Li; Xuexia Miao (Journal of Pest Science, 2017)

Isolation of fourteen novel polymorphic microsatellite markers for alien or invasive species: monitoring and management of the mud snail Bullacta exarata Philippi, 1849 - Xiaoying Li; Yu Leng; Zhiguo Dong; Yiting Liu; Ruobing Wen; Xudong Liu; Peiming He (Conservation Genetics Resources, 2014)

A pair of chiral flavonolignans as novel anti‐cyanobacterial allelochemicals derived from barley straw ( H ordeum vulgare ): characterization and comparison of their anti‐cyanobacterial activities - Xi Xiao; Haomin Huang; Zhiwei Ge; Trine B. Rounge; Jiyan Shi; Xinhua Xu; Ruobing Li; Yingxu Chen (Environmental Microbiology, 2014)
Summary The inhibitory effect of barley straw ( H ordeum vulgare ) on cyanobacteria has been observed in many field and laboratory studies for over 30 years, although the compounds responsible for this anti‐cyanobacterial effect have remained unknown. In this study, a pair of chiral flavonolignans were isolated from barley straw extract using a bioassay‐guided isolation procedure against M icrocystis sp. The structures of the allelopathic compounds were elucidated by NMR (nuclear magnetic resonance) and HPLC‐MS (high performance liquid chromatography‐mass spectrometry), and turned out to be salcolin A and B . The enantiomers differ in their anti‐cyanobacterial abilities. Both enantiomers exhibited inhibitory effects on M icrocystis sp ., and the EC 50 (concentration for 50% of maximal effect) of salcolin A and B were 6.02 × 10 −5 and 9.60 × 10 −5 mol l −1 , respectively. Furthermore, the modes of actions of the enantiomers were investigated and compared at a single cell level by flow cytometry. Salcolin A was found to induce an increase on cyanobacterial intracellular ROS (reactive oxygen species) levels and to inhibit esterase activity, whereas salcolin B caused leakages of cyanobacterial cytoplasms. Thus, salcolin A was more ‘algistatic’, and salcolin B was more ‘algicidal’. This study suggests that salcolin is the key allelochemical in barley straw's inhibitory effect on cyanobacteria and could be used as an agent in the future control of cyanobacterial harmful algae blooms.